Mechanical responses of a shallow-buried super-large-section tunnel in weak surrounding rock: A case study in Guizhou. (January 2023) - Zhao, Jinpeng; Tan, Zhongsheng; Yu, Rongsen; Li, Zonglin; Wang, Xiuying
Graphical abstract: Highlights: A rare super-large-section tunnel with four-lane was studied in this study. The responses of the tunnel with shallow-buried depth were obtained by on-site monitoring. Suggestions for the design and construction of the super-large-section tunnel with four-lane. Abstract: With the gradual increase in traffic demand, the cross-sectional sizes of tunnels are increasing. Consequently, significant attention has been given to the complexity of the mechanical responses of super-large-section tunnels. Based on a super-large-section tunnel of 21.6 m (four-lane) in Qichong Village, Guizhou Province, China, the mechanical responses of the tunnel construction process in the weak surrounding rock were studied using on-site monitoring. The mechanical responses were summarized through the deformation analysis of vertical displacement and horizontal convergence, as well as through the comparison with the existing case of the longitudinal displacement profile. The surrounding rock pressure, shotcrete stress, steel set stress, and axial stress of the bolts were also analyzed. The unique mechanical construction characteristics of the super-large-section of the tunnel with a low flat ratio were observed, and the corresponding technical suggestions for super-large-section tunnels were proposed. This study enriches the database and provides a reference for similar super-large-section tunnels.